New fixed point results in fuzzy metric space - Soumeyeh Khaleghizadeh (Journal of Hyperstructures, 2021)
In this paper, we introduce certain new classes of contraction mapping and establish fixed point theorems for such kindof mapping in triangular fuzzy metric spaces.